Methodology to Measure the Effectiveness of Social Services - Irina Yuryevna Vaslavskaya; Irina Alexandrovna Koshkina; Alfiya Ruslanovna Fattakhova; Sabina Damirovna Khakimova; Victor Alexandrovich Fursov (International Review of Management and Marketing, 2016)
This article considers such problems as evaluating the effectiveness of social services and public needs financing. Due to the fact that social services are provided and funded by state or local authorities, assessment of their effectiveness requires special tools. Existing legally defined methods have several drawbacks and do not provide an objective picture. A comparative analysis of estimates according to official methodology and the author's empirical research are present in this article. On this basis, the conclusion about need for a different approach of providing the state (municipal) services is formulated.